Analysis Of The Effectiveness Of The Implementation Of E-Performance At The Office Of The Department Of Trade And Industry Of Gowa Regency - Artati Artati; Ikram Idrus; Edi Jusriadi; Ahmad AC Ahmad AC (Green Publisher Indonesia, 2024)
Performance appraisal is an important instrument in measuring the contribution of individuals and teams in achieving organizational goals. Digital transformation, including the implementation of e-performance, is an important strategy to optimize employee performance and improve organizational efficiency, especially in the context of local government. This research analyzes the implementation of e-performance at the Trade and Industry Office of Gowa Regency, as well as the factors that influence its success. Qualitative methods were used by taking samples of employees and leaders who mastered the e-performance system. The results show that the implementation of e-performance has improved compliance, smooth routines, and the expected impact in managing employee performance. Supporting factors include leadership awareness and commitment, adequate information technology infrastructure, and employee training. However, there is a lack of acceptance of the need for innovation as an inhibiting factor. Positive employee disposition towards change and management support in providing the necessary resources and guidance are key to successful implementation of e-performance.